(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The present paper looks into the structure of sentences used by the author. It is evident fromthe text that the author frequently deviates from the norms. Her style is inclined towards the spoken form.There are features like ellipses, prefaces and noun-phrase tags, fragments etc. Much has to be inferredfrom the context and surroundings. Type of sentences and word order are selected to convey specificmeanings.